In vitro potential cytotoxicity of an adhesive system to alveolar macrophages - Porto,Isabel Cristina Celerino de Moraes (2009)
The purpose of this study was to evaluate the potential cytotoxicity of Adper Single Bond 2 (SB) simplified etch-and-rinse adhesive system in alveolar macrophage cultures, as a function of the post-polymerization time and duration of immersion in the culture medium for preparation of extracts, by observing the levels of nitric oxide (NO) release and cell survival rate (MTT assay). Wistar rat alveolar macrophages were exposed to 200 μL of extracts obtained from 24- or 72-h immersion of adhesive samples in culture medium (RPMI), immediately or 24 h after polymerization. Fresh RPMI and E. coli lipopolysaccharides were used as negative and positive controls, respectively. The cells were placed in a humidified incubator for 24 h. The results were analyzed by the Student's-t test (α=5%). The amount of NO produced and viable cells were significantly different (p<0.05) between the experimental and the control groups, showing that, irrespective of the post-polymerization time and duration of immersion in the culture medium, the adhesive system caused intense cytotoxicity to the macrophages. The cytotoxic effects were not statistically different (p<0.05) among the experimental groups. In conclusion, chemical components released from SB in aqueous environment were highly toxic to cell culture and thus an inflammatory pulpal response should be considered during the clinical application of dental adhesives.